Ultralow Power Wearable Heterosynapse with Photoelectric Synergistic Modulation - Tian‐Yu Wang; Jia‐Lin Meng; Zhen‐Yu He; Lin Chen; Hao Zhu; Qing‐Qing Sun; Shi‐Jin Ding; Peng Zhou; David Wei Zhang (Advanced Science, 2020)
Abstract Although the energy consumption of reported neuromorphic computing devices inspired by biological systems has become lower than traditional memory, it still remains greater than bio‐synapses (≈10 fJ per spike). Herein, a flexible MoS2‐based heterosynapse is designed with two modulation modes, an electronic mode and a photoexcited mode. A one‐step mechanical exfoliation method on flexible substrate and low‐temperature atomic layer deposition process compatible with flexible electronics are developed for fabricating wearable heterosynapses. With a pre‐spike of 100 ns, the synaptic device exhibits ultralow energy consumption of 18.3 aJ per spike in long‐term potentiation and 28.9 aJ per spike in long‐term depression. The ultrafast speed and ultralow power consumption provide a path for a neuromorphic computing system owning more excellent processing ability than the human brain. By adding optical modulation, a modulatory synapse is constructed to dynamically control correlations between pre‐ and post‐synapses and realize complex global neuromodulations. The novel wearable heterosynapse expands the accessible range of synaptic weights (ratio of facilitation ≈228%), providing an insight into the application of wearable 2D highly efficient neuromorphic computing architectures.